Engineered T cells for cancer treatment - Anurathapan, Usanarat (2013)
Adoptively transferred T cells have the capacity to traffic to distant tumor sites, infiltrate even fibrotic tissue and kill antigen-expressing tumor cells. A variety of groups have investigated different genetic engineering strategies designed to enhance tumor specificity, increase T cell potency, improve proliferation, persistence, or migratory capacity, and increase safety. In this review we focus on recent developments in the T cell engineering arena, discuss the application of these engineered cell products clinically, and outline future prospects for this therapeutic modality.